Tui Na for painful peripheral neuropathy in people with human immunodeficiency virus: A randomized, double-blind, placebo-controlled trial protocol - Zhu, Xingmei; Ge, Song; Dune, Linda; Yang, Chao; Tian, Chong; Wang, Yong (Frontiers in Neurology, 2023)
Background Peripheral neuropathy (PN), including numbness, loss of sensation, paresthesia, a burning sensation, and stabbing pain in extremities, is a common complication in people with human immunodeficiency virus (PHIV). Medications commonly used to treat HIV-related PN are not effective and lead to many side effects. HIV-related PN symptoms may be alleviated or treated with a series of therapeutic Chinese foot massages (TCFM), which are non-invasive and relatively safe. However, relevant studies are lacking. Study design This proposed trial is a prospective, two-arm, parallel, double-blinded, randomized controlled trial. Aim This proposed trial aims to assess the effectiveness of TCFM on HIV-related PN in people with HIV (PHIV). Outcomes The primary outcomes, measured at baseline, end of TCFM/placebo, and twelve weeks after, include (1), lower extremity pain, (2) lower extremity functioning, and (3) health-related quality of life. The secondary outcomes, measured throughout the trial process, include (1) recruitment and completion rate (No. of referred, No. of eligible, No. of enrolled, No. of withdrawals, trial recruitment rate, and trial completion rate), (2) participants' safety (No. and severity of adverse events), (3) treatment adherence (average time of each message session, No. of completed sessions, and No. of missed sessions), and (4) compliance (No. of participants completing the trial following the initial group assignment). Sample size An estimated 142 participants in total, or 71 participants in each arm, will be needed for this trial. Trial status This trial was registered at ClinicalTrials.gov of the National Institute of Health on Oct 26, 2022 (ClinicalTrials.gov Identifier: NCT05596123). The researchers expect to recruit participants starting in Feb. 2023 and ending in Feb 2025.